CULINARY TOURISM FESTIVAL AS LEARNING MEDIA IN VOCATIONAL EDUCATION: EFFECTS ON STUDENT SATISFACTION - Rezki Alhamdi; Eryd Saputra (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
As a form of experiential learning, culinary tourism festivals provide opportunities for students to engage directly with real-world industry practices. This study aims to evaluate the overall quality of culinary festivals held in Batam City and examine their role as learning media for students in tourism and hospitality programs. The research specifically involves students who have participated in culinary festivals in Batam, allowing them to assess the quality of the festivals from an experiential learning perspective. A quantitative research method was employed, and data were analyzed using Smart-PLS. The results indicate that food quality and taste, as well as program content, significantly influence visitor satisfaction. However, the element of local food does not have a significant impact on satisfaction. Furthermore, satisfaction was found to have no significant effect on word-of-mouth behavior. These findings are expected to contribute to the enhancement of students' learning experiences during culinary tourism programs and support the development of effective experiential learning strategies in vocational education, particularly in the context of tourism and hospitality studies in Batam City.